Compulsory Secondary Schooling in Argentina: Policies for social and educational inclusion at school - Bocchio, María Cecilia (2018)
In Argentina, Compulsory Secondary Schooling (CSS) is a component of the National Education Law No. 26.206 enacted in 2006, and it is translated into a set of intervention strategies designed by the national government and the provincial governments. This paper aims at analyzing policies oriented to educational and social inclusion, which are translated into plans, programs, and projects that are enacted (Ball et al., 2012) at schools. Speeches given and texts produced by the Federal Council of Education in 2003 and subsequent years were revised. Then, plans, programs, and projects designed within the CSS framework were identified, and the enactment of these social and educational policies in different provinces of Argentina was approached by recovering local and own investigations. Finally, some conflicts related to management by projects were addressed, as a constant variable in CSS policies, promoted in the school every day and over the challenge of ensuring the democratization of compulsory schooling.